IMPACTS OF CLIMATE AND REGULATION ON ICE-JAM FLOODING OF NORTHERN RIVERS AND THEIR INLAND DELTAS - Rokaya, Prabin 1987- (2018)
In cold region environments, ice-jam floods (IJFs) are important hydrological and hydraulic events that play an important role in floodplain ecology but also pose a major concern for citizens, authorities, insurance companies and government agencies, primarily because they can result in high water depths in rivers that can exceed levees leading to devastating floods. In the past 35 years, there have been significant advances in river ice hydrology. However, understanding on several aspects of IJFs still remains limited. Little work has been carried out on investigating how the frequency and severity of IJFs have been changing or might change in the future. Similarly, IJF delineation remains a significant challenge even for streams and small rivers. There is also still substantial progress to be made in quantifying the effects of climate variability and regulation on IJFs. This dissertation addresses some of these existing knowledge gaps. First, it reviews the recent advances in IJF research and identifies existing gaps, challenges and opportunities. With a changing environment, there are implications for river ice processes and this dissertation work investigates some of the potential implications particularly how the timing and magnitude of breakup flows that lead to IJFs are changing at local and regional levels. Literature review shows IJF research has been highly site specific but this dissertation also offers regional and global perspectives. Climate and anthropogenic factors are likely to have unequal localized effects. Some regions might be more resilient and others, such as high latitude northern regions, might be more vulnerable. Thus, local implications for river ice processes and current and future probabilities of IJFs are assessed for two river basins in western Canada. The findings from the Athabasca River at the town of Fort McMurray show that the probability of ice-jam flooding in the future will be lower but extreme IJF events are still probable. The results from the town of the Peace River in ...